2022
DOI: 10.1111/fare.12767
|View full text |Cite
|
Sign up to set email alerts
|

Relationship satisfaction during COVID‐19: The role of partners' perceived support and attachment

Abstract: Objective The main goal of this study was to examine the interplay between individuals' attachment insecurity and their perceptions of their partners' COVID‐related behaviors (supportive and negative behaviors) in predicting their relationship satisfaction. Background Stress is a well‐documented risk factor for relationship satisfaction. COVID‐19 related stressors thus pose a challenge to maintaining relationship satisfaction. Although partners' supportive behaviors can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
1
3
0
Order By: Relevance
“…Regarding the mediating effect of own conflict strategies between attachment and relationship satisfaction, the current study showed that withdrawal was a mediator between avoidant attachment and relationship satisfaction. These results follow other studies that found the negative effect of individuals’ behavior in relationship satisfaction in response to COVID‐19‐related stress (e.g., Bar‐Shachar et al, 2023). Although our results did not find differences between the association between avoidant attachment, withdrawal, and relationship satisfaction in confined and in non‐confined individuals, this lack of difference could be due to the length of the confinement.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding the mediating effect of own conflict strategies between attachment and relationship satisfaction, the current study showed that withdrawal was a mediator between avoidant attachment and relationship satisfaction. These results follow other studies that found the negative effect of individuals’ behavior in relationship satisfaction in response to COVID‐19‐related stress (e.g., Bar‐Shachar et al, 2023). Although our results did not find differences between the association between avoidant attachment, withdrawal, and relationship satisfaction in confined and in non‐confined individuals, this lack of difference could be due to the length of the confinement.…”
Section: Discussionsupporting
confidence: 91%
“…Although our results did not find differences between the association between avoidant attachment, withdrawal, and relationship satisfaction in confined and in non‐confined individuals, this lack of difference could be due to the length of the confinement. Certainly, as Bar‐Shachar et al (2023) pointed out, deactivation and distancing strategies deployed by avoidantly attached individuals over a prolonged period of time may negatively impact both objective and subjective stress. All of this, in turn, could end up negatively impacting relationship satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…During pandemic lockdowns, couples often were confined at home to deal with these stressors isolated from larger support networks. These extraordinary challenges motivated numerous studies documenting the impact of the pandemic on relationships, which confirmed expectations based on existing theories in relationship science (Pietromonaco & Overall, 2021): Couples who experienced greater pandemic stress and had pre-existing vulnerabilities, such as attachment insecurity, showed declines in relationship quality during the pandemic (Haydon & Salvatore, 2022;Schmid et al, 2021;Pauly et al, 2022), but couples who were able to be responsive and supportive fared better (e.g., Bar-Shachar et al, 2023;. Additionally, some studies, but not all, found that couples experienced greater conflict and lower relationship quality during early stages of the pandemic (see .…”
Section: Did Relationship Quality During the Covid-19 Pandemic Vary A...mentioning
confidence: 56%
“…This is surprising considering the extensive research that shows the relation between the internal working model and proximity‐seeking behaviors (Lavy et al, 2010; Mikulincer & Shaver, 2007; Snir & Wiseman, 2010) and may be explained as follows: First, it may be that joint‐drawing raises issues that relate more extensively to present relational dynamics between partners and to gender‐role socialization than to the internal working model, which is based on experiences with past attachment figures. Although past experience influences the internal working model and interpersonal relationships, there is evidence that current relationships, among them with romantic partners, influence and expand the repertoire of attachment behaviors of adults (Bar‐Shachar et al, 2023; Constant et al, 2021; Mónaco et al, 2022; Wang et al, 2022). What's more, the ECR focuses on close relationships in general and does not place emphasis on the current relationship.…”
Section: Discussionmentioning
confidence: 99%